Electrical and optical properties of heavily Ge-doped AlGaN. (28th January 2019) - Blasco, R; Ajay, A; Robin, E; Bougerol, C; Lorentz, K; Alves, L C; Mouton, I; Amichi, L; Grenier, A; Monroy, E
Abstract: We report the effect of germanium as n-type dopant on the electrical and optical properties of Al x Ga1− x N layers grown by plasma-assisted molecular-beam epitaxy. The Al content has been varied from x = 0 to 0.66, confirmed by Rutherford backscattering spectrometry, and the Ge concentration was increased up to [Ge] = 1 × 10 21 cm −3 . Even at these high doping levels (>1% atomic fraction) Ge does not induce any structural degradation in Al x Ga1− x N layers with x < 0.15. However, for higher Al compositions, clustering of Ge forming crystallites was observed. Hall effect measurements show a gradual decrease of the carrier concentration when increasing the Al mole fraction, which is already noticeable in samples with x = 0.24. Samples with x = 0.64–0.66 remain conductive ( σ = 0.8–0.3 Ω −1 cm −1 ), but the donor activation rate drops to around 0.1% (carrier concentration around 1 × 10 18 cm −3 for [Ge] ≈ 1 × 10 21 cm −3 ). From the optical point of view, the low temperature photoluminescence is dominated by the band-to-band emission, which shows only the spectral shift and broadening associated to the Burstein–Moss effect. The evolution of the photoluminescence peak position with temperature shows that the free carriers due to Ge doping can efficiently screen the potential fluctuations induced by alloy disorder.